The Landscape and its Literature, in the change of philosophical paradigm (Simbiótica. Revista Eletrônica, 2022)
This article is based on the definition of the concept of landscape, on the perspective of philosophy of nature and the environmental philosophy, and its relationship with the representation of the landscape in literature. In its investigative pathway, it unveils the aesthetic and ethical experience of nature, which evolves from the concept of conservation to the category of environment, with its economic, social, cultural, and historical correlations, configured in what we call "cultural landscapes", marked by the dilemma "sustainable growth or development". And then, analysis the new paradigm of nature, where the human being is integrated, which emanated from the concept of environment and drive into the construction of a new aesthetic and a new ethics, a new environmental philosophy, premonitorily represented in literature.Keyword: Nature; Environnement; Cultural landscape; Environmental philosophy.